دور إدارة المخاطر الائتمانية في استمرارية ونجاح المؤسسات المصرفية - دردوري, د/لحسن (Sciences humaines, 2015)
تواجه معظم المؤسسات المالية المصرفية حالة عدم التأكد في العديد من الأنشطة التي تقوم بها،حيث تواجه أنواعا عديدة من المخاطر بالنظر إلى طبيعة نشاطها، لذلك تلجا المؤسسات المصرفية لتكوين نظام كفؤ لإدارة المخاطر التي تواجهها من اجل تحقيق أهدافها وتحسين خدماتها وضمان منافسة المؤسسات الأخرى لكي تبني لنفسها مركزا بارزا ولكي تنمو وتستمر،لذلك تحتاج إدارات المؤسسات المالية والمصرفية إلى تهيئة بيئة مناسبة وتحديد أهداف واستراتيجيات لإدارة المخاطر،وذلك من خلال إرساء نظم وقواعد قادرة على تحديد وقياس احتمالات التعرض للمخاطر والسيطرة عليها لمواجهة آثارها. Most financial banking institutions facing uncertainty in many of the activities carried out, as they face many types of risk given the nature of their activities, so resorted banking institutions to create an efficient system for managing risks in order to achieve their goals and improve their services and ensure competition and other institutions to adopt for itself a prominent center and in order to grow and continue, so you need the financial and banking institutions departments to create an appropriate setting targets environment and risk management strategies, and through the establishment of rules and regulations is able to identify and measure the likelihood of exposure to risk and control them to face the consequences.